Exploring Applications of ChatGPT to English Language Teaching: Opportunities, Challenges, and Recommendations - Kostka, Ilka; Toncelli, Rachel (TESL-EJ (Berkeley, Calif.), 2023)
By utilizing a massive corpus of textual data, large language models can generate unique human-like outputs to questions and interact with users in a natural conversational way. ChatGPT is one such platform, and since it emerged into the public consciousness in November 2022, it has generated both excitement and concern among educators. A growing body of scholarship has considered the pedagogical use of ChatGPT and its ability to enhance teachers’ roles (e.g., Kohnke et al., 2023; Rudolph et al., 2023). Scholars have also raised concerns about ChatGPT’s impact on academic integrity and scholarly publishing (Teng, 2023). Nonetheless, AI has existed for some time (Holmes & Tuomi, 2022) and, rather than a beginning of the end of education, it may guide educators into an era of pedagogical innovation (Heaven, 2023). In this paper, we explore the role of ChatGPT in English Language Teaching (ELT). We first provide background information about ChatGPT and its functions. We then draw from literature to describe current thinking on its benefits and challenges then describe how we have experimented with ChatGPT at our own university. We conclude by discussing implications for using ChatGPT in ELT and offering recommendations for future directions in teaching and research.